Landsat derived patterns of lake drainage in northern Alaska between 1975-2019 - Mark Lara; Yaping Chen; Benjamin Jones (Arctic Data Center, 2021)
Forty-five years (i.e. 1975-2019) of Landsat observations were used to map the spatiotemporal patterns of lake drainage in northern Alaska. All Landsat data was pre-processed by the United States Geological Survey and downloaded by google earth engine in a radiometrically, atmospherically, and geometrically terrain-corrected state. We used Landsat surface reflectance products acquired from the Multispectral Scanner (MSS), Terrestrial Mapper (TM), Enhanced Terrestrial Mapper Plus (ETM+), and Operational Land Imager (OLI) sensors to compute eight image mosaics for the ice-free period (June 15 to September 1) at five-year time-periods. This data product represents the change in lake area between time-periods or epochs. All data used to spatially identify patterns of lake change are presented in a map (LakeDrainChg.tif), where the associated morphometric controls on drainage are summarized for each of the ~33,000 lake boundaries (Lake_Drainage.shp). All data can also be viewed within Google Earth Engine (https://code.earthengine.google.com/?accept_repo=users/mjlara71/LakeDrainage; accessed on 13 September 2021) or clone Git repository (git clone https://earthengine.googlesource.com/users/mjlara71/LakeDrainage accessed on 13 September 2021).